2017
DOI: 10.1097/qai.0000000000001179
|View full text |Cite
|
Sign up to set email alerts
|

An HIV Preexposure Prophylaxis Demonstration Project and Safety Study for Young MSM

Abstract: Background Young men who have sex with men (YMSM) are a key population for implementation of PrEP interventions. This open-label study examined adherence to PrEP and assessed sexual behavior among a diverse sample of YMSM in 12 U.S. cities. Methods Eligible participants were 18–22 year old HIV-uninfected MSM who reported HIV transmission risk behavior in the past 6 months. Participants were provided daily TDF/FTC (Truvada®). Study visits occurred at baseline, monthly through week 12, then quarterly through w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
243
1
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(263 citation statements)
references
References 35 publications
13
243
1
6
Order By: Relevance
“…Some studies have shown that older age is associated with greater adherence as measured by drug levels [8, 10]. Adolescent Trials Network (ATN) 113 and ATN 110—U.S.-based studies that tested the acceptability, safety, and adherence to PrEP among 78 MSM ages 15–17 years and 200 MSM 18–24 years, respectively—show lower adherence among these groups than what has been described in adult studies [14**,15]. In ATN 110, over 90% of participants had some detectable drug level through the first 12 weeks of the study, and over 50% had levels consistent with at least 4 pills per week.…”
Section: Adolescent and Young Adult Adherence To Prepmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that older age is associated with greater adherence as measured by drug levels [8, 10]. Adolescent Trials Network (ATN) 113 and ATN 110—U.S.-based studies that tested the acceptability, safety, and adherence to PrEP among 78 MSM ages 15–17 years and 200 MSM 18–24 years, respectively—show lower adherence among these groups than what has been described in adult studies [14**,15]. In ATN 110, over 90% of participants had some detectable drug level through the first 12 weeks of the study, and over 50% had levels consistent with at least 4 pills per week.…”
Section: Adolescent and Young Adult Adherence To Prepmentioning
confidence: 99%
“…By week 48, protective levels of drug were detected in only 34% of participants. Racial disparities in adherence were described; median drug levels for black participants were below the protective threshold at all time points [14**]. In ATN 113, the majority of participants reached protective drug levels through 12 weeks, with similar drop off at 24 weeks, when visits became less frequent [15].…”
Section: Adolescent and Young Adult Adherence To Prepmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to PrEP is essential, and new ways to support MSM in appropriate use of PrEP are much needed (eg, mobile phone applications) 30. Appropriate use of PrEP entails adherence to the daily medication, and correct use of the medication in situations or periods of increased risk for HIV for those following a non-daily regimen.…”
Section: Pre-exposure Prophylaxis For Msmmentioning
confidence: 99%
“…According to a 2015 surveillance report, the New Orleans Metairie area was ranked 3rd based on rate (per 100,000) of HIV diagnosis [33]. The Adolescent Trials Network (ATN) 110 Study in New Orleans screened a total of 200 gay, transgender, bisexual youth (GTBY) between January and September 2013 and found 9 to be acutely infected, demonstrating the magnitude of the problem in this population [35].…”
Section: Design and Populationmentioning
confidence: 99%